1976
DOI: 10.1055/s-0028-1104151
|View full text |Cite
|
Sign up to set email alerts
|

Wirkung von Nitroglycerin beim akuten Myokardinfarkt. II. Intravenöse Dauerinfusion von Nitroglycerin bei Patienten mit und ohne Linksinsuffizienz und ihre Auswirkungen auf die Infarktgröße

Abstract: Twenty-four patients with acute myocardial infarction were divided into two groups according to left-ventricular filling pressure (LVFP): group I (n = 13) with LVFP less than 20 mm Hg, group II (n = 11) with LVFP greater than 20 mm HG. After infusion of 3 mg nitroglycerin in the first and 6 mg in the second hour there was a highly significant decrease in the filling pressure (from 15 to 9 mm Hg in group I, 28 to 16 mm Hg in group II). Mean arterila pressure fell in both groups by an average of 9 mm Hg. There w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

1980
1980
1991
1991

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(8 citation statements)
references
References 5 publications
1
7
0
Order By: Relevance
“…Other authors also found that cardiac out put remained unchanged or increased in the patients with initially elevated left ventricu lar filling pressure, but tended to decrease when it was lower than 18 mm Hg [1,13,14], Flaherty [15] found similar results with the most beneficial effects on cardiac output in the patients evidencing the most severe heart failure. However, he also showed that the patients with abnormal baseline ejection fraction had an improvement of ejection fraction with an early NTG administration while those with late NTG had not.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Other authors also found that cardiac out put remained unchanged or increased in the patients with initially elevated left ventricu lar filling pressure, but tended to decrease when it was lower than 18 mm Hg [1,13,14], Flaherty [15] found similar results with the most beneficial effects on cardiac output in the patients evidencing the most severe heart failure. However, he also showed that the patients with abnormal baseline ejection fraction had an improvement of ejection fraction with an early NTG administration while those with late NTG had not.…”
Section: Discussionsupporting
confidence: 65%
“…Intravenous nitroglycerin (NTG) is found to be a very effective therapy in patients with acute myocardial infarction due to its multiple beneficial effects in reducing in farct size, major infarct complications and improving global left ventricular function [1][2][3][4][5], Several studies demonstrated NTGinduced hypotension in some patients with acute myocardial infarction [2,6,7] and the others showed that low mean arterial pres sure could abolish these beneficial effects [3,8],…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, during continuous hemody namic monitoring, the fall in mean arterial pressure was small. Furthermore, 35-lead precordial maps showed no evidence of in creased myocardial injury' [1], Meanwhile different groups have pre sented data which confirm the positive ef fects of nitrates in patients with myocardial infarction and various degrees of heart fail ure [4,[6][7][8][9][10][11][12][13][14][15], Detailed analysis of the studies con ducted in the past decade revealed that pri marily patients who have elevated filling pressures will benefit from nitrate therapy as is shown by an increase of cardiac output, an improvement of clinical status and a de crease of infarct-related complications [8,10,11,14], In a study of Bussmann et al [8] 60 patients with acute myocardial infarction who had diastolic pulmonary artery pres sures higher than 15 mm Hg (mean 20 mm Hg) were enrolled. The patients were ran domly allocated to either intravenous nitro glycerin or placebo.…”
Section: Nitrates In Acute Myocardial Infarctionmentioning
confidence: 84%
“…Bussmann et al [7] could show that 10 mg ISDN orally led to a significant de crease of left ventricular filling pressure and to a significant increase of cardiac output. Dose augmentation up to 30 mg was effec tive with regard to pressure lowering for at least 5 h.…”
Section: Nitrates In Acute Myocardial Infarctionmentioning
confidence: 99%
See 1 more Smart Citation